The Involvement of Human Amnion in Histologic Chorioamnionitis is an Indicator that a Fetal and an Intra-Amniotic Inflammatory Response is More Likely and Severe: Clinical Implications - Park, Chan-Wook (2008)
OBJECTIVE: Amnionitis (inflammation of the amnion) is the final stage of extra-placental chorioamniotic inflammation. We propose that patients with “amnionitis”, rather than “chorionitis” have a more advanced form of intra-uterine inflammation/infection and, thus, would have a more intense fetal and intra-amniotic inflammatory response than those without “amnionitis”. STUDY DESIGN: The relationship between the presence of amnionitis, and a fetal and an intra-amniotic inflammatory response was examined in 290 singleton preterm births (36 weeks) with histologic chorioamnionitis. The fetal inflammatory response was determined by plasma C-reactive protein (CRP) concentrations in umbilical cord and the presence of funisitis. The intra-amniotic inflammatory response was assessed by matrix metalloproteinase-8 (MMP-8) concentration and white blood cell (WBC) count in 156 amniotic fluid (AF) samples obtained within 5 days of birth. AF was cultured for aerobic and anaerobic bacteria and genital mycoplasmas. The CRP concentration was measured with a highly sensitive immunoassay. RESULTS: (1) Amnionitis was present in 43.1% of cases with histologic chorioamnionitis. (2) Patients with amnionitis had a significantly higher rate of funisitis and positive AF culture and a higher median umbilical cord plasma CRP, AF MMP-8 level and AF WBC count than those without amnionitis (p < 0.001 for each). (3) Among cases with amnionitis, the presence or absence of funisitis was not associated with significant differences in the median cord plasma CRP, AF MMP-8 level and AF WBC count. (4) However, the presence of amnionitis in cases with funisitis was associated with a higher median umbilical cord plasma CRP, AF MMP-8 level and AF WBC count than the absence of amnionitis in those with funisitis (p < 0.05 for each). (5) Multiple logistic regression analysis demonstrated that amnionitis was a better independent predictor of proven or suspected early-onset neonatal sepsis (odds ratio 3.8, 95% confidence interval (CI) 1.1–13.2, p < 0.05) than funisitis (odds ratio 1.8, 95% CI 0.5–6.1, not significant) after correction for the contribution of other potential confounding variables. CONCLUSION: The involvement of the amnion in the inflammatory process of the extraplacental membranes is associated with a more intense fetal and intra-amniotic inflammatory response than chorionitis alone. This observation has clinical implications because it allows staging of the severity of the inflammatory process and assessment of the likelihood of fetal involvement.